Allostery in BAX Protein Activation. - Jiang, Zhenyan; Zhang, Hansi; Böckmann, Rainer (Journal of biomolecular structure & dynamics, 2015)
BAX is a member of the proapoptotic BCL-2 family of proteins, which is involved in the regulation of the intrinsic pathway of apoptosis. In the process of apoptosis, BH3-only molecules activate cytosolic BAX. Activated BAX molecules insert into the mitochondrial outer membrane (MOM) with their a9-helix and form oligomers that lead to membrane poration, resulting in the release of apoptogenic factors including cytochrome c. Recently, a novel interaction site for the binding of the BIM SAHB ligand to BAX was reported. BIM SAHB binding was shown to invoke the exposure of the 6A7 epitope (amino acids 13 - 19) and of the BH3 domain of BAX, followed by mobilization of the BAX a9-helix. However, the intramolecular pathway for signal transmission in BAX, from BIM SAHB binding to mobilization of the a9-helix largely remained elusive. For a molecular understanding of the activation of BAX and thus the first steps in apoptosis, we performed microsecond atomistic molecular dynamics simulations both of the BAX protein and of the BAX:BIM SAHB complex in aqueous solution. In agreement with experiment, the 6A7 and BH3 domains adopt a more solvent exposed conformation within the BAX:BIM SAHB complex. BIM SAHB binding was found to stabilize the secondary structure of the a9-helix. A force distribution analysis revealed a force network of residue-residue interactions responsible for signal transmission from the BIM SAHB binding site predominantly via the a4- and a6-helices to the a9-helix on the opposite site of the protein.